DESAIN KATALOG RAJA KANTOR 2016 - Andini Dwi Cahyani (Politeknik Negeri Jakarta, 2016)
ABSTRACTRaja Kantor need promotion media for his own to information his product which own by them. So, to information his product he makes a catalog namely